Choice of law and recognition in Asian family law - Lui, Wilson; Nishioka, Kazuaki; Reyes, Anselmo (Studies in private international law. Asia, 2023)
This thematic volume in the series Studies in Private International Law - Asia outlines the general choice of law and recognition rules relating to family matters of 15 Asian jurisdictions: Mainland China, Hong Kong, Taiwan, Japan, South Korea, Singapore, Malaysia, Vietnam, Cambodia, Myanmar, the Philippines, Indonesia, Thailand, Sri Lanka and India. The book examines pressing questions and proposes ways in which their systems may be reformed. A concluding chapter considers the extent to which Asian cross-border family law systems can and should be harmonised.The book provides a comprehensive analysis of cross-border family law challenges, including child surrogacy, child abduction, the recognition of same-sex unions, the recovery of maintenance, and the regulation of intercountry adoption. These are among the matters now testing Asian institutions of private international law and acting as forces for their modernisation.With contributions by leading Asian private international law experts, the book proposes necessary reforms for each of the jurisdictions analysed as well as for Asia as a whole.